As easy as riding a bike? How mandatory bicycle helmet laws may harm those who can least afford it. (September 2019) - Dellora, Carlo
This work takes compulsory helmet laws in Victoria and considers them from a new angle – namely that of someone living with a disability. While much has been written on mandatory helmet laws in terms of their broader societal implications, little has been done on their impact on society's most vulnerable such as the disabled, the impecunious and the mentally impaired. Drawing on the author's time at the Melbourne Magistrates' Court as a framework, this article analyses the existing state of the law and provides a critique of its shortcomings – prosecuting the argument that existing legislation can have an unexpected impact upon the marginalised in our community, particularly those with a cognitive impairment.